1995
DOI: 10.1016/0014-5793(95)01377-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional characterization of a rat brain Kvβ3 potassium channel subunit

Abstract: A novel potassium channel l~-subunit (K,~3) was cloned from rat brain being the third member of a K~iB subunit gene family. It is a protein of 403 amino acid residues with a 68% amino acid sequence homology to K,~I.1. KJ]3 is primarily expressed in rat brain having a distribution distinct to those of K~I.1 and K~2. This subunit also has a long N-terminal structure and induces inactivation in N-terminal deleted K~l.4 but not in other members of the K~I channel family. Similarly to K,i~l.1, the K,~3-induced inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…1 C). We observed a significant increase in expression of the mature band but not immature Kv1.2 upon coexpression with Kvβ, indicating increased maturation and cell surface stability, consistent with previous reports (Shi et al, 1996; Heinemann et al, 1995; Li et al, 2000). Kv1.2 protein expression was significantly decreased with Slc7a5, for both the mature and immature forms.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1 C). We observed a significant increase in expression of the mature band but not immature Kv1.2 upon coexpression with Kvβ, indicating increased maturation and cell surface stability, consistent with previous reports (Shi et al, 1996; Heinemann et al, 1995; Li et al, 2000). Kv1.2 protein expression was significantly decreased with Slc7a5, for both the mature and immature forms.…”
Section: Resultssupporting
confidence: 92%
“…We previously reported that coexpression with Slc7a5 suppresses Kv1.2 currents and protein expression in various cell lines, accompanied by a combination of pronounced gating effects (Baronas et al, 2018). Given the well-established effects of Kvβ subunits on gating and Kv1.2 cell surface maturation and expression (Shi et al, 1996; Heinemann et al, 1995; Li et al, 2000), we sought to determine the regulatory effects of Kvβ and Slc7a5 on Kv1.2. We first established that coexpression of Kv1.2 with Kvβ1.2 (Kvβ) in LM mouse fibroblast cells (1:4 transfection ratio) led to coassembly, which we confirmed by observing a rapidly inactivating current upon depolarization to +60 mV (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Application of DTT alone readily reverses the effects of cysteine oxidation in many proteins, including voltage-gated K + channels (Ruppersberg et al 1991; Rettig et al 1994; Heinemann et al 1995). Therefore, this observation that application of DTT alone failed to reverse the effect of Ch-T to increase the Slo current amplitude suggests that reversible oxidation of cysteine may not mediate this phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidized cysteine is easily reduced back by the reducing agent DTT. For example, N-type inactivation in Kv1.4 and Kv1.4/Kvβ is slowed by oxidation in a cysteine-dependent manner and this effect is readily reversed by DTT (Ruppersberg et al 1991; Rettig et al 1994; Heinemann et al 1995). The observation that the decreased Slo channel current induced by patch excision and H 2 O 2 is restored by DTT implicates cysteine oxidation as the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%